Pengaruh Social Media Marketing Terhadap Brand Loyalty Yang Dimediasi Oleh Brand Trust Pada Pelanggan Smartphone Samsung - Diansyah; Putri, Annisa Navalia; Suryono, Imam (Future Science, 2025)
The purpose of this study is to determine the effect of social media marketing on brand loyalty mediated by brand trust. This study was conducted with the aim of explaining quantitatively. The population in this study were customers or users of Samsung smartphone products who actively use social media. The sampling technique used was convenience simple random sampling with a sample size of 95. The data analysis method used in this study was the Structural Equation Model (SEM) with a measurement model using the Smart PLS program. The results of this study indicate that social media marketing has a significant effect on brand trust. Social media marketing has a significant effect on brand loyalty. Brand trust shows a significant effect on brand loyalty. Brand trust can mediate the influence of social media marketing on brand loyalty.